Insights from the draft genome of the subsection V (Stigonematales) cyanobacterium Hapalosiphon sp. Strain MRB220 associated with 2-MIB production. Issue 1 (December 2016) - Tan, Boon; Te, Shu; Boo, Chek; Gin, Karina; Thompson, Janelle
Abstract A non-axenic unialgal culture containing a Subsection V (Stigonematales) cyanobacterium, Hapalosiphon strain MRB 220, was obtained from a benthic freshwater algal mat through multiple transfers following growth in sterile media. Physiological characterization demonstrated the culture was capable of nitrogen-fixation and production of the off flavor compound 2-methylisoborneol (2-MIB). Total DNA isolated from this culture was sequenced using Illumina HiSeq andde novo assembled into contigs. The genome of MRB 220 was separated from co-occurring heterotrophic bacteria using sequence homology and compositional approaches, and its purity was confirmed based on best BLAST hit classification and principle component analysis of the tetranucleotide frequencies of fragmented contigs. The genome of ~7.4 Mbp contains 6, 345 protein coding genes with 4, 320 of these having functional prediction including predicted pathways for biosynthesis of the secondary metabolite welwitindolinone. Analyses of 16S rRNA gene and whole genome sequence average nucleotide identity indicated close relatedness of MRB 220 to the generaHapalosiphon andFischerella within the order Stigonematales. Microscopic examination showed that MRB 220 formed heterocystous branched filaments, thereby supporting identification of strain MRB 220 as a morphospecies ofHapalosiphon . Availability of the draft genome ofHapalosiphon strain MRB 220 enables future work to elucidate the pathway and dynamics for biosynthesis of 2-MIB and other secondary metabolites and understand the ecology and physiology of Stigonematales cyanobacteria in tropical freshwaters.